PENDAMPINGAN PERPAJAKAN BAGI UMKM DI DESA KERINJING KECAMATAN TANJUNG RAJA KABUPATEN OGAN ILIR - Umi Kalsum; Mukhtaruddin; Kencana Dewi; Rika Henda Safitri; Yulia Saftiana; Luk Luk Fuadah (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Abstract Taxation is a hot topic of discussion, especially in the Covid-19 Pandemic Era with the policies in the taxation sector taken by the Government, including for people who have Micro, Small and Medium Enterprises (MSMEs). The purpose of this community services is to provide tax socialization to MSMEs Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency. The target audience of this activity is the MSMEs community who are not well acquainted with taxation, both in the general and specifically regarding the MSMEs behind this activity. This community Services is carried out directly face to face because the nature of this activity is that apart from socializing it also provides assistance related to taxation to the MSMEs community and based on the result of questionnaires from respondents, positive feedback is obtained from the MSMEs community for the activities that have been carried out. Keywords: Tax, MSMEs.